Performance of a special tractor as a function of ballasting and front-wheel drive in coffee harvesting - Tavares, Tiago de Oliveira [UNESP]; Borba, Matheus Anaan de Paula [UNESP]; Gallo, Luís Alexandre Michelli [UNESP]; Gírio, Lucas Augusto da Silva [UNESP]; Paixão, Carla Segatto Strini [UNESP]; da Silva, Rouverson Pereira [UNESP] (Coffee Science, 2018)
One of the main concerns before agricultural mechanization is the fuel cost from an economic and environmental point of view. In some literature, it has been demonstrated that the adequacy of tractors is directly related to consumption, which may become a strategy to reduce it. However, the studies were performed with conventional tractors, without information on how the special coffee tractors behave to the adequacy. In this respect, the aim of the present study was to evaluate the hourly fuel consumption in six possible adjustments of a special tractor in the operation of mechanized coffee harvesting. A 4x2 FWD tractor was used, with 52.2 kW power and 2400 kg mass, with 40% to the front axle and 60% to the rear to pull a Master Café 2 coffee harvester with 2900 kg mass without load. The treatments consisted of three ballast configurations in the tractor whether or not using auxiliary front-wheel drive (FWD). The adopted mass-power ratios were: 48, 52 and 56 kg kW-1; obtained through the quantitative alteration of liquid and solid ballasts of the tractor, respecting the mass distribution between the axles recommended by the tractor manufacturer. The evaluations consisted of monitoring fuel consumption at regular hourly intervals, following the premises of statistical process control. It is concluded that the mass-power ratio of 56 kg kW-1 with driven FWD should be used in order to obtain lower slipping, lower average hourly fuel consumption and higher quality.
Desempenho de um trator especial em função da lastragem e do acionamento tração dianteira auxiliar no recolhimento de café
Keywords: Fuel consumption; Operating balance; Statistical process control